Post-Covid-19 Impacts on Socio-economic and Livelihood Patterns: An Empirical Study on Rural Bangladesh - Shanta, Mahbuba Akter; Suman, Shihab Uddin; Kibria, Md Golam (South Asian Journal of Social Sciences and Humanities, 2025)
The COVID-19 pandemic had a devastating impact on local livelihoods as a result rapid vulnerabilities have been arising after the pandemic in the rural areas of Bangladesh. This study tried to show the crucial impacts of post-COVID-19 on socio-economic and livelihood patterns on Bangladeshi lower-income group people including employment, agricultural, and business sectors working people. This study employed a mixed-method approach, including both qualitative and quantitative methods, and following the convenience sampling method, a total of 300 respondents were interviewed for quantitative data and 25 in-depth interviews for qualitative information from three sectors of the rural areas of the Satkhira district of Bangladesh. Research findings showed that, Chi-square calculated value is = 13.20054 and Critical value or chi-square tabular value is = 12.59159 that’s indicates Calculated value > Critical value 13.20054 > 12.59159 so the Null hypothesis (There is no severe impact of post COVID-19 on local livelihoods) is rejected and the Alternative hypothesis (There is severe impact of post COVID-19 on local livelihoods) is accepted. Major findings are that there were crucial effects of the pandemic on the socio-economic well-being of the marginal people, then the crucial impacts on their livelihood patterns, job uncertainty, etc. At the end of this study, this paper will require support from the relevant authorities to undertake measures for the well-being of the vulnerable group of people from the agriculture sector, business sector & employment sector to continue their functions. So to minimize the worst impacts of post COVID-19 on local livelihoods immediate policy responses and Govt. assistance are required in both these sectors.